2020
DOI: 10.3389/fonc.2020.533176
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulation of CCT-3 Induces Breast Cancer Cell Proliferation Through miR-223 Competition and Wnt/β-Catenin Signaling Pathway Activation

Abstract: The clinical significance and the function of chaperonin-containing TCP1 complex 3 (CCT-3) in breast cancer remain unknown. In this study, we found that CCT-3 was markedly overexpressed in breast cancer tissues. Statistical analysis revealed a significant correlation of CCT-3 expression with advanced breast cancer clinical stage and poorer survival. Ablation of CCT-3 knocked down the proliferation and the tumorigenicity of breast cancer cells in vitro and in vivo. CCT-3 may regulate breast cancer cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Overexpression of CCT3 increased b-catenin in MDA-MB-231 and T47D breast cancer cells, which could be modulated by microRNA (miRNA) 223. This miRNA was shown to bind to the 3′UTR of both CCT3 and b-catenin (65). The conclusion drawn from this study was that CCT3 mediates breast cancer growth by binding to and competitively inhibiting miRNA 223.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Overexpression of CCT3 increased b-catenin in MDA-MB-231 and T47D breast cancer cells, which could be modulated by microRNA (miRNA) 223. This miRNA was shown to bind to the 3′UTR of both CCT3 and b-catenin (65). The conclusion drawn from this study was that CCT3 mediates breast cancer growth by binding to and competitively inhibiting miRNA 223.…”
Section: Discussionmentioning
confidence: 69%
“…Herein, we showed that CCT2 expression can upregulate MYC and CCND1 gene expression and promote metastatic-like behavior in luminal A breast cancer cells that are typically less aggressive than the basal-like/TNBC subtypes usually associated with MYC amplification. Others reported that overexpression or suppression of CCT3 in basal-like TNBC cells altered cell proliferation and changed the expression of MYC (64,65). One pathway of interest is WNT/b-catenin signaling that regulates cell growth and could drive proliferation in breast can cer cells throug h MYC an d CCN D1 (6 6 , 6 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…CCT, a cytosolic chaperonin in eukaryotes, has been best elucidated in its interactions with the cytoskeletal proteins actin and tubulin 9 ; meanwhile, as to the role of CCT in cancers, extensive studies have disclosed that CCT promotes the cancer cell growth and tumorigenicity through affecting the expression of MYC, cyclin D1, and regulating the Wnt/β‐Catenin signaling pathway 20,21 . CCT6A belongs to the subunit of CCT, which is firstly reported in 2006, among which, CCT6A is identified in drug‐resistant melanoma and is reported to play an important role in the regulation of cancers 15,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The first gene codes for thioredoxin reductase 1, an intracellular redox sensor and antioxidant enzyme whose deregulation may be involved in breast cancer initiation [ 55 ]. CCT3 protein product is the chaperonin containing TCP1 subunit 3, a component of a complex which catalyses the correct folding of proteins involved in cytoskeletal assembly and the cell cycle and whose involvement in the promotion of breast cancer cell proliferation and metastasis via Wnt has been recently acknowledged [ 56 , 57 ]. It is also of note that one of the most significant Gene Ontology (GO) terms in which a large amount of the genes validated by Liang et al [ 54 ] were enriched was the “Wnt signaling pathway”, which is known to be highly dysregulated in breast tumor [ 58 ].…”
Section: Molecular Signatures In Breast Cancer Cellsmentioning
confidence: 99%